Intermittent hypoxic conditioning: experience and potential in cardiac rehabilitation programs - O. S. Glazachev; N. P. Lyamina; G. K. Spirina (Российский кардиологический журнал)
The review describes the experience in intermittent hypoxic conditioning protocols in rehabilitation programs for patients with cardiovascular diseases. Based on randomized controlled trials, the efficacy and safety of intermittent hypoxic conditioning in patients with cardiovascular disease, including those with multicomorbidity in clinical practice, have been analyzed. From a physiological and clinical standpoints, the review justifies the need for further controlled clinical trials on hypoxic conditioning with a longer follow-up period both to expand the clinical indications for this method and to develop optimal combinations with exercise within cardiac rehabilitation programs. Discovery of the key mechanisms of adaptation to oxygen concentration changes and further research on hypoxia physiology will expand the application of this method in clinical and rehabilitation medicine in cardiac patients.